Likes and dislikes of teachers for their school and out-of-school activities in Nagcarlan, Laguna - Balantakbo, Teodora (Lirio) 1916- (s.n.], 1971)
This paper is an attempt to explore the likes and dislikes of public elementary school teachers in this locality. The data for this study were gathered through a checklist of all possible activites from the public elementary school teachers of Nagcarlan, Laguna.